Desarraigo cultural en la tejedora de coronas. (2021)
Germán Espinosa, one of the great Colombian writers, is the author of the novel «La Tejedora de coronas» (The weaver of crowns) (in which he recreates the siege of Cartagena -which is a historic landmark in our country’s history- from the point of view of Genoveva Alcocer. This woman is the narrator-protagonist of the story; from her critical conscience as a cultural subject immersed in the culture of the corrupted but prudish XVIII century society, she trascends her vision of it, travels to the Enlightment Europe of that century where she mingles with many of the contemporaneous great thinkers - Voltaire among them- and witness the knowledge revolution that is going on. When she returns to her home town with the idea of transforming the mentality of her fellow citizens, she is condemned and burned by the Inquisition. The story develops from the vision of this rebellious, critic, sexy and aggressive woman while the author develops an analysis of its cultural subject who is presented as assuming her culture, then evaluating and criticizing it, then attepmting to impose other models for the which the Cartagena people perhaps were not prepared yet.